Editors' Choice—Vibrational Properties of Oxygen-Hydrogen Centers in H+- and D+-Implanted Ga2O3. (23rd December 2020) - Portoff, Amanda; Venzie, Andrew; Qin, Ying; Stavola, Michael; Fowler, W. Beall; Pearton, Stephen J.
Abstract : The ion implantation of H + and D + into Ga2 O3 produces several O–H and O–D centers that have been investigated by vibrational spectroscopy. These defects include the dominant VGa(1) -2H and VGa(1) -2D centers studied previously along with additional defects that can be converted into this structure by thermal annealing. The polarization dependence of the spectra has also been analyzed to determine the directions of the transition moments of the defects and to provide information about defect structure. Our experimental results show that the implantation of H + (or D + ) into Ga2 O3 produces two classes of defects with different polarization properties. Theory finds that these O–H (or O–D) centers are based on two shifted configurations of a Ga(1) vacancy that trap H (or D) atom(s). The interaction of VGa(1) -nD centers with other defects in the implanted samples has also been investigated to help explain the number of O–D lines seen and their reactions upon annealing. Hydrogenated divacancy VGa(1) -VO centers have been considered as an example.